Additive manufacturing of a compliant mechanism using Zr-based bulk metallic glass - Jan Wegner; Maximilian Frey; Ralf Busch; Stefan Kleszczynski (Additive Manufacturing Letters, 2021)
Compliant mechanisms offer several advantages compared to rigid mechanisms, such as lower friction, backlash, and reduced part count which makes them attractive for structural and medical applications. However, their motion is limited by the elastic properties of the used material. Bulk metallic glasses offer a unique combination of high strength and large elastic deformation which suggests a high potential for the application in compliant mechanisms. This unique property profile originates from the amorphous structure, which results from the rapid cooling of tailored glass-forming alloy compositions. Recently, additive manufacturing via laser powder bed fusion established as a pivotal technology to overcome the limitations of size and complexity during the fabrication of bulk metallic glasses. This work presents the fabrication of a compliant mechanism via laser powder bed fusion that utilizes the unique elastic properties of the Zr59.3Cu28.8Al10.4Nb1.5 bulk metallic glass forming alloy in combination with the geometrical freedom of additive manufacturing.